ILLOCUTION IN SPEECH ACTS BY FOREIGN STUDENTS IN INDONESIAN AS A FOREIGN LANGUAGE CLASSES - Latifah Tri Budiasih; Andayani Andayani; Muhammad Rohmadi (Center of Language and Cultural Studies [CLCS], 2017)
This research explores illocution in speech acts by foreign students in Indonesian as a Foreign Language classes at Sebelas Maret University. Illocution is a speech that shows the state of language relating to the situation in general and more free and aims to express something from the speaker to the partner. This research aims to describe the forms of student illocution in Indonesian Language classes. This study used qualitative approach with naturalistic design. Data were collected using observation, interviews, and document analysis. The data of illocution acts included assertive, declaration, directives, commissive, and expressive in learning activities. The study revealed that students applied assertive, directives, commissive and expressive as their main speech acts during learning Indonesian language in the classroom especially in the oral uses for communications.